Musculatura craneal de tres especies del género Liophis (Serpentes: colubridae) - Moro, Silvia Alejandra (1994)
The cranial muscles of three argentinian species of the genus Liophis is described. They present a typical colubroid anatomy, with some interspecific variations. A new muscle of the group of Constrictores dorsalis is described in Liophis sagittifer and L. poecilogyrus. Their cranial anatomy has been compared with that of other species near Liophis, leading to the proposal that they are closely related to of Lystrophis, Xenodon and Waglerophis.